2012
DOI: 10.1097/mcg.0b013e31823712cc
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Bacterial Colonization of Pancreatic Stents Used in Endoscopic Retrograde Cholangiopancreatography

Abstract: Colonization of PSs by pathogenic organisms is common and related to duration in situ of the PS. Enteric organisms are frequently implicated. Although significant clinical sequelae are infrequent, we suggest that PSs should not be left in situ for >7 to 10 days due to the significant risk of bacterial colonization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…Ascending bacterial colonization can occur through retrograde migration from the intestinal lumen (more likely after pancreatic surgery) or through the formation of a biofilm on the surface of pancreatic duct stents . More specifically, a recent study by Hill et al . cultured pancreatic duct stents placed by a single operator at a tertiary referral center and reported that 28 of 47 stents grew clinically significant bacteria, and the majority of which belonged to the Enterobacteriaceae family of gram‐negative bacteria, a finding consistent with our report.…”
Section: Discussionsupporting
confidence: 90%
“…Ascending bacterial colonization can occur through retrograde migration from the intestinal lumen (more likely after pancreatic surgery) or through the formation of a biofilm on the surface of pancreatic duct stents . More specifically, a recent study by Hill et al . cultured pancreatic duct stents placed by a single operator at a tertiary referral center and reported that 28 of 47 stents grew clinically significant bacteria, and the majority of which belonged to the Enterobacteriaceae family of gram‐negative bacteria, a finding consistent with our report.…”
Section: Discussionsupporting
confidence: 90%
“…In regard to the route of bacterial invasion from the intestine to the pancreas, we found that preoperative stent placement was one of the independent risk factors of bacterial contamination (odds ratio 6.7, P = .025). It is likely that sphincterotomy performed for stent placement allowed bacteria to invade the main pancreatic duct . This story mirrors that in previous studies of biofilm covering pancreatic duct stents .…”
Section: Discussionsupporting
confidence: 69%
“…Though gut appears to be the main source of bacteria for stent occlusion, at times gram-positive bacteria, such as, Staphylococcus aureus, Enterococcus, and anaerobes can also be found. Hill et al 28 reported bacterial growth composed of bacteria, such as, Klebsiella, Escherichia, Enterobacter, and Enterococcus in 28/47 retrieved pancreatic stents, with a strong correlation between the duration of indwelling stents and the bacterial growth. The species diversity of pancreatic stent biofilms was further testified in a study that characterized more than 246 resident species.…”
Section: Pancreatic Biofilmsmentioning
confidence: 99%